Effects of Rare Earth Elements and Nitrogen Co‐Doped on the Photocatalytic Performance of TiO2. Issue 2 (16th January 2018) - Bao, Ruiyu; Yu, Yanmin; Chen, Huiying; Wang, Wenzhong; Xia, Jianxin; Li, Hua
Abstract: Titanium dioxide (TiO2 ), which is codoped with nine different rare earth mental ions (RE 3+ = lanthanum (La 3+ ), cerium (Ce 3+ ), praseodymium (Pr 3+ ), neodymium (Nd 3+ ), samarium (Sm 3+ ), gadolinium (Gd 3+ ), erbium (Er 3+ ), ytterbium (Yb 3+ ), lutetium (Lu 3+ )) and nitrogen (N), are synthesized by non‐hydrolytic sol‐gel method under different calcination temperatures. The morphology, structure and performance of as‐prepared samples are characterized by X‐ray diffraction (XRD), scanning electron microscope (SEM), X‐ray photoelectron spectroscopy (XPS), UV‐vis diffuse reflectance spectroscopy (DRS) and ultraviolet‐visible absorption spectroscopy. The results indicat that co‐doping can inhibit the particles growth significantly and extend light‐absorption to the visible region. Nd/N and Pr/N co‐doped TiO2 (calcining temperature at 380 °C) exhibit superior photocatalytic activity toward methyl orange (MO) degradation under visible light irradiation for 150 min, the degradation rate of MO solution are approximately 91 and 89% respectively. By comparison, the degradation rate are only 43 and 7% for the N‐TiO2 and pure TiO2 respectively. Abstract : Titanium dioxide, which is codoped with nine different rare earth ions and nitrogen, are synthesized by non‐hydrolytic sol‐gel method under different calcinations temperatures. The results indicate that co‐doping can inhibit the particles growth and extend light‐absorption to the visible region. Nd/N‐TiO2 and Pr/N‐TiO2 (380 °C) exhibit superior photocatalytic activity toward methyl orange degradation under visible light irradiation, the degradation rates are approximately 91 and 89% respectively.